The Interactions between Labour Market Policies and Income Inequalities in Groups of European Union Countries - Szulc‑Obłoza, Agnieszka; Szczepaniak, Małgorzata (Comparative Economic Research. Central and Eastern Europe, 2024)
Social cohesion and a sustainable labour market remain the aims of sustainable development policy. However, income inequalities and labour market policies are more often separately analysed. To fill the identified research gap, our article presents the results of an analysis of interactions between active and passive labour market policies and income inequalities in the European Union. The 27 countries were divided into two clusters based on their active and passive labour market policy (LMP) expenditures in 2019. These clusters sustain the basis for analysing the interactions between LMP and income inequalities in its different measures. The results reveal that labour market interventions interact with income inequalities, decreasing disposable income inequalities (equalising the disposable income after transfers and taxes) and therefore contributing to social cohesion. This paper concerns social cohesion as the manifestation of intragenerational justice.